12PImpact of β-catenin phosphorylation patterns on tumour control/progression in a prospective cervical cancer study (RAIDs). (7th November 2019) - Scholl, S; Latouche, A; De Koning, L; Popovic, M; de la Rochefordière, A; Berns, E; Gestraud, P; Girard, E; Lecerf, C; von der Leyen, H; Roman Roman, S; Rouzier, R; et al.
Abstract: Background: Between 2013 and 2017, the RAIDs consortium conducted a European biobanking study, [BioRAIDs (NCT02428842)] aiming at prospectively annotating cervical cancer (CC) patients and identifying molecular patterns associated with outcome. Dominant oncogenic alterations were reported in PIK3CA (40%), while dominant suppressor gene alterations were seen in KMT2D (15%) and KMT2C (16%). A "metagene" combining these alterations was associated with outcome (https://doi.org/10.1016/j.ebiom.2019.03.069 ). Methods: WES and RPPA data together with PFS at 24 months are available in 89 patients. A boosting approach based on a solid theoretical framework, able to cope with high-dimensional data and censored survival end-points, allowed the identification of innovative potential prognostic markers. Results: At a median follow up (FU) of 24 months, progression-free survival (PFS) rates of this FIGO stage IB1-IV population, treated predominantly (87%) by chemoradiation, were 65.4% [CI95%: 60.2-71.1]. In the present analysis, beyond viral clade and FIGO stage, a number of RPPA phospho-protein parameters came up as relevant predictors, associated with better or poorer outcome. Of particular interest is the detection of two different sites for β-catenin phosphorylation (at serine residues 552 and 675), which were associated with prediction of extremes of positive or negative outcome. Conclusions: Proteasome-dependant posttranslational modifications to a low molecular weight form of β-catenin phophorylated at COOH-terminal residue S552 has been shown to enhance nuclear translocation and β-catenin/TCF reporter activation possibly through association with histone acetylases (doi: 10.1038/s41598-017-18421-8). Phospho-β-catenin S552 and S675 may predict CC tumor control/progression in patients who failed DNA repair pathway inhibition. Ongoing studies attempt to better define the role of different β-catenin phosphorylations and molecular forms in the BioRAIDS population. Clinical trial identification: NCT02428842. Legal entity responsible for the study: Institut Curie. Funding: The European Union's Seventh Program for Research, Technological Development and Demonstration under Grant agreement No 304810 and the Fondation ARC pour la Recherche Contre le Cancer. Disclosure: All authors have declared no conflicts of interest.